Interspace and Vacancy Modulation: Promoting the Zinc Storage of an Alcohol‐Based Organic–Inorganic Cathode in a Water–Organic Electrolyte. Issue 47 (17th October 2022) - He, Weidong; Lin, Zedong; Zhao, Kangning; Li, Yanlu; Meng, Chao; Li, Jiantao; Lee, Sungsik; Wu, Yongzhong; Hao, Xiaopeng
Abstract: Expanding interspace and introducing vacancies are desired to promote the mobility of Zn ions and unlock the inactive sites of layered cathodes. However, this two‐point modulation has not yet been achieved simultaneously in vanadium phosphate. Here, a strategy is proposed for fabricating an alcohol‐based organic–inorganic hybrid material, VO1− x PO4 ·0.56C6 H14 O4, to realize the conjoint modulation of the d ‐interspace and oxygen vacancies. Peculiar triglycol molecules with an inclined orientation in the interlayer also boost the improvement in the conversion rate of V 5+ to V 4+ and the intensity of the PO bond. Their synergism can ensure steerable adjustment for intercalation kinetics and electron transport, as well as realize high chemical reactivity and redox‐center optimization, leading to at least 200% increase in capacity. Using a water–organic electrolyte, the designed Zn‐ion batteries with an ultrahigh‐rate profile deliver a long‐term durability (fivefold greater than pristine material) and an excellent energy density of ≈142 Wh kg −1 (including masses of cathode and anode), thereby substantially outstripping most of the recently reported state‐of‐the‐art zinc‐ion batteries. This work proves the feasibility to realize the two‐point modulation by using organic intercalants for exploiting high‐performance new 2D materials. Abstract : A new organic–inorganic hybrid material, VO1− x PO4 ·0.56C6 H14 O4, with enriched oxygen defects and tunable d ‐interspace, is designed and used as a model platform to systematically elucidate the correlation of some physicochemical properties. Coordination between the water–organic electrolyte and molecular engineering, an ultrahigh‐rate profile, high capacity, and long‐life are achieved for Zn‐ion batteries.